2017
DOI: 10.1002/ijc.30615
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of group 1 p21‐activated kinases suppresses pancreatic stellate cell activation and increases survival of mice with pancreatic cancer

Abstract: Pancreatic cancer remains one of the most lethal of all solid tumors. Pancreatic stellate cells (PSCs) are primarily responsible for the fibrosis that constitutes the stroma and p21-activated kinase 1 (PAK1) may have a role in signalling pathways involving PSCs. This study aimed to examine the role of PAK1 in PSCs and in the interaction of PSCs with pancreatic cancer cells. Human PSCs were isolated using the modified outgrowth method. The effect of inhibiting PAK1 with group 1 PAK inhibitor, FRAX597, on cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Activated PSCs play a pivotal role in the pathologic processes of pancreatic diseases, and inhibition of PSCs activation, or even the transformation of activated PSCs into quiescence PSCs, has been found to be benecial to the treatment of pancreatic cancer and pancreatitis. [18][19][20] The activated PSCs are positive for a-SMA, collagen 1, so this two molecules are oen used as the marker of PSCs activation. 21 As shown in Fig.…”
Section: Inhibition Of Asic1a Suppresses the Activation Of Pscs Inducmentioning
confidence: 99%
“…Activated PSCs play a pivotal role in the pathologic processes of pancreatic diseases, and inhibition of PSCs activation, or even the transformation of activated PSCs into quiescence PSCs, has been found to be benecial to the treatment of pancreatic cancer and pancreatitis. [18][19][20] The activated PSCs are positive for a-SMA, collagen 1, so this two molecules are oen used as the marker of PSCs activation. 21 As shown in Fig.…”
Section: Inhibition Of Asic1a Suppresses the Activation Of Pscs Inducmentioning
confidence: 99%
“…α-SMA is an established marker for PSC activation [27], and its expression is negatively correlated with PDA survival [28]. We have previously reported that inhibition of PAK1 decreased proliferation and increased apoptosis of PSCs while suppressing SMA expression in PSCs [12]. Here for the first time we have detected the expression of -SMA by both Western blot and immunofluorescent staining in cells established from xenografts isolated from pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 83%
“…Inhibition of PAK1 synergistically with gemcitabine reduced the growth of pancreatic cancer cells in vitro and in vivo [10], and activation of PAK1 contributed to gemcitabine resistance of pancreatic cancer cells [11]. Inhibition of PAK1 also suppressed PSC activation and proliferation while promoting apoptosis, and deletion of stromal PAK1 increased survival of mice with PDA [12]. PAK4 promoted PDA cell proliferation and survival by activation of the NF-κB pathway [13], and inhibition of PAK4 increased the sensitivity of PDA cells to gemcitabine [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed the role of PAK1 in PSC modulation for the first time by showing that inhibition of PAK1 by FRAX597 (a potent group I PAK inhibitor) reduced the activation and proliferation of PSC and increased apoptosis in vitro . In an orthotopic pancreatic cancer mouse model, survival in the PAK1 knockout group was significantly increased compared to the PAK1 wildtype group, and depletion of PAK1 in the pancreatic stroma also reduced PAK1 expression and activity in the tumour[ 64 ]. Similarly, survival was prolonged in the group treated with FRAX597 plus gemcitabine in the same orthotopic pancreatic cancer model[ 59 ].…”
Section: Pak Signalling In Pancreatic Cancermentioning
confidence: 99%
“…The extensive desmoplastic reaction, which is a hallmark of pancreatic cancer, is reported to result in a dense stroma, deficient vascularization and inefficient drug delivery, eventually leading to chemo-resistance[ 96 , 97 ]. As mentioned above, PAK1 is responsible for PSC activation, leading to stromal fibrosis[ 64 ] in pancreatic cancer similar to its pivotal role in liver fibrogenic pathways[ 98 ].…”
Section: Paks and Chemo-resistance In Pancreatic Cancermentioning
confidence: 99%